1977
DOI: 10.1136/adc.52.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cord bilirubin levels with hyperbilirubinaemia in ABO incompatibility.

Abstract: SUMMARY We studied 91 offspring of ABO incompatible pregnancies and 30 controls resulting from 0-0 pregnancies to test whether cord bilirubin levels could be used to predict the severity of hyperbilirubinaemia in ABO incompatibility. Blood group, direct Coombs's test, and serum bilirubin estimations were carried out on cord blood, and bilirubin estimations at 12, 24, 36, and 48 hours of life.All newborns in whom the cord bilirubin was greater than 4 mg/100 ml (68 ,umol/l) developed severe hyperbilirubinaemia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 12 publications
2
32
1
1
Order By: Relevance
“…This study reported significant jaundice and anemia through infants with positive direct coombs test. Same results were published by Risembery et al [14].…”
Section: Discussionsupporting
confidence: 77%
“…This study reported significant jaundice and anemia through infants with positive direct coombs test. Same results were published by Risembery et al [14].…”
Section: Discussionsupporting
confidence: 77%
“…Risemberg et al al noted a strong associa on of strongly posi ve coombs test with hyperbilirubinaemia in ABO incompa bilty 9 . In Moderately aff ected group 9 (60%) were DCT posi ve out of total 15 babies.…”
Section: Discussionmentioning
confidence: 96%
“…HM Rusemerg et al reported ABO incompa bility in 20-25% of deliveries and ABO haemoly c disease in less than 10% of these cases 9 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations